Teaching English Speaking Skill through Pair and Group Interview Techniques - Sudirman Maca (Universitas Cokroaminoto Palopo, 2020)
The problem that the participants face in the speaking class teaching is very low confident in speaking English in the class. The research aims are to find the effectiveness the pair and group interview techniques to enhance the participants’ speaking skill. The experimental study consisting 100 participants at fourth semester of Educational English Department Bosowa University and 40 participants have been chosen randomly as a sample which divided into the treatment class and control class. The treatment class was divided into pairs and groups in conducting the three types of interview techniques in which, one participant asking the four participants and four participants asking one student. The study reveals that the participants felt free and brave expressed their language skill through the small group both pairs and groups of interview techniques. Moreover, these result also was identified that these techniques effective stimulating the participants to speak English actively, confidently, and fluently than the traditional teaching model. In which, all the treatment class, most the participants speaking English actively, whereas the control class is only 60 percent participants speaking English actively and some of the participants only kept silent in the class.